Follicular mucinosis in a teenage girl - Rupnik, Helena (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Follicular mucinosis is characterized by mucin deposits within the hair follicles and sebaceous glands. It can occur as a primary idiopathic benign disorder; it can be found as an incidental phenomenom in rare cases of different dermatoses; or it can arise as a secondary symptom of a malignant disorder, most commonly mycosis fungoides. Youth and localization in a single area used to be regarded as indicative of the benign nature of follicular mucinosis. However, recent reports demonstrate that no clear-cut criteria allow for the differentiation of idiopathic from lymphoma-associated follicular mucinosis. We report the case of a 16-year old girl who presented with a 2-year history of a single, slightly pruritic, erythematous patch on the left side of the neck. Different local treatments (local corticosteroids, antibiotics, antifungal ointments and moisturizers) were ineffective. Overall,she was healthy. Histopathological examination of the lesion showed the typical histological picture of follicular mucinosis.
Keywords: Adolescenca; Adolescence; dermatologija; Mikoza fungoidna; mikoze; mladostniki; Mucinosis, Follicular; Mucinoza folikularna; Mycosis Fungoides